The Effect of Nasal Spray Preservatives Benzalkonium Chlorid and Potassium Sorbate On Rat Nasal Mucosa. (Annals of Medical Research, 2021)
None
Keywords: Benzalkonium chlorid, Potassium sorbate, Nasal mucosa.